Employee Performance Improvement Strategy through Motivational Approach and Competitive Compensation System - Yuaniko Paramitra; Hana Sabda Prilia (SAN Scientific, 2026)
This study aims to analyze the influence of work motivation and compensation on employee performance at Pertamina Ciputat gas station, South Tangerang. In facing competition in the era of globalization and technological advancement, companies are required to maintain and improve the quality of human resource performance. Work motivation in this study is measured based on Maslow's theory of needs which includes physiological needs, safety, social, self-esteem, and self-actualization. Meanwhile, compensation includes salary, incentives, insurance, facilities, and benefits. The study used a quantitative approach by distributing questionnaires to 40 respondents. The results of the regression analysis showed that both work motivation and compensation have a positive and significant effect on employee performance, both partially and simultaneously. The most dominant indicator in influencing motivation is the need for safety, while in compensation is insurance, and in the performance aspect is honesty. These findings demonstrate the importance of the role of management in creating a safe, fair, and supportive work environment to increase productivity and employee loyalty sustainably.